(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Biodiesel has its unique position in the field of renewable energy as alternate fuel to diesel due to fuel price, energy requirement and petroleum crisis. In this study, biodiesel was produced from Waste Cooking Oil (WCO) using Copper doped Zinc Oxide (CZO) nanocatalysts. The synthesized Copper doped Zinc Oxide nanocatalysts were characterized by X-Ray Diffraction (XRD) and High Resolution Transmission Electron Microscope (HRTEM). Design of experiment was framed using Taguchi method to limit the experiments and to find the optimum reaction conditions. The effect of process parameters such as oil-to-methanol ratio (O/M), catalyst type, catalyst concentration, temperature and time on the transesterification reactions using characterized Copper doped Zinc Oxide nanocatalyst were investigated. The 4% (weight /weight) nanocatalyst concentration, 1:5 Oil to methanol molar ratio at 60Â°C temperature and 40 minutes of reaction time were found to be optimum, in which the maximum biodiesel yield of 98 % (w/w) was obtained. Hence it was determined that nanocatalysts exhibited good catalytic activities on biodiesel production from Waste Cooking Oil (WCO).